COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE IN SUPPORTING REGIONAL AUTONOMY IMPLEMENTATION (STUDY ON TULUNGAGUNG AND TRENGGALEK REGENCY) - Mudrifah S.E; Gugus Irianto, SE., MSA., Ph.D., Ak. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research aims to know and compare about financial performance in Tulungagung and Trenggalek regency from 2006-2010 fiscal year to support regional autonomy implementation. The data sources were from the documentations which was taken from DPPKAD Tulungagung Regency and Directorate General of Financial Development (www.djpk.depkeu.go.id) analysed by using descriptive comparative method with some financial ratios, the ratio of financial independence regency, financial effectiveness, the degree of fiscal decentralization, the ratio of capital expenditures, the ratio of expenditure management, and growth ratios. The result of this research showed that the financial independence of Tulungagung regency was 7, 76% higher than 6,53 % ratio of Trenggalek regency. However, both of them is in the 0-20% range therefore they have instructive pattern. The financial effectiveness of Tulungagung and Trenggalek regency in the late five years was stable over 100%. Therefore it is very efective to both of them. The efectiveness means either Tulungagung regency or Trenggalek regency are able to implement PAD target. The result of capital expenditure ratio, showed that Trenggalek regency has higher rate, 17,68 %, meanwhile Tulungagung regency only has 16,45%. The result of expenditure management ratio shown that Tulungangung regency has 92, 72% rates, and Trenggalek has 97, 42% rates. However, the growth of financial capabilty of Trenggalek and Tulungagung regency is good because it has increased from 2006-2010, although it is very small increasing. Overall, the financial capability both of Tulungagung and Trenggalek Regency is still in the low level to support regional autonomy implementation. So, the government needs to have an effort to increase PAD either from extensification or intensification by identifying regency potential to increase financial source by improving performance of tax collection.